Sensitiveness of Porous Silicon‐Based Nano‐Energetic Films. Issue 6 (28th July 2016) - Plummer, Andrew; Kuznetsov, Valerian A.; Gascooke, Jason; Shapter, Joe; Voelcker, Nicolas H.
Abstract: Nanoporous silicon (pSi) films on a silicon wafer were loaded with sodium perchlorate and perfluoropolyether (PFPE) oxidizing agents. Sensitiveness to impact, friction and electrostatic discharge (ESD) of the resulting energetic thin films were investigated. It was observed that pSi loaded with perchlorate was sensitive at the lowest limit of detection for the available equipment (<4.9 J impact energy, <5 N friction force, and <45 mJ ESD spark energy). When loaded with PFPE the material was very sensitive to impact (<4.9 J), moderately sensitive to ESD (between 45 and 100 mJ) and insensitive to friction (>360 N). pSi loaded with either perchlorate or PFPE displayed behavior during sensitiveness testing similar to other primary explosive materials. Abstract :